SIGNIFICANCE OF D-DIMER AND FERRITIN INDICATORS IN PATIENTS WITH VARIOUS SEVERITY LEVELS OF COVID-19. (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
Although most patients who have had COVID-19 recover and return to their initial state, some of them still have persistent health problems, and this process is called post-acute COVID syndrome or long COVID. The World Health Organization defines long COVID as the continuation of disease symptoms for three months or more after the initial infection and the occurrence of new symptoms in the absence of other causes. The opinion of experts from the aforementioned reputable organization has been confirmed by a number of other observations.